A novel wearable device for continuous, non-invasion blood pressure measurement. (August 2017) - Xin, Qin; Wu, Jianping
Abstract: In this paper, we have developed a wearable cuffless device for daily blood pressure (BP) measurement. We incorporated the light based sensor and other hard wares in a small volume for BP detection. With optimized algorithm, the real-time BP reading could be achieved, the data could be presented in the screen and be transmitted by internet of things (IoT) for history data comparison and multi-terminal viewing. Thus, further analysis provides the probability for diet or sports suggestion and alarm. We have measured BP from more than 60 subjects, compare to traditional mercury blood pressure meter, no obvious error in both systolic blood pressure (SBP) and diastolic blood pressure (DBP) are detected. Such device can be used for continues non-invasion BP detection, and further data docking and health analysis could be achieved.